2016
DOI: 10.1007/s11745-016-4177-2
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil and Microalga Omega‐3 as Dietary Supplements: A Comparative Study on Cardiovascular Risk Factors in High‐Fat Fed Rats

Abstract: Dietary supplementation with marine omega-3 polyunsaturated fatty acids (n-3 PUFA) can have beneficial effects on a number of risk factors for cardiovascular disease (CVD). We compared the effects of two n-3 PUFA rich food supplements (freeze-dried Odontella aurita and fish oil) on risk factors for CVD. Male rats were randomly divided into four groups of six animals each and fed with the following diets: control group (C) received a standard diet containing 7 % lipids; second group (HF high fat) was fed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Guelzim et al [ 20 ] showed that n-3 PUFAs could improve the body composition and insulin sensitivity and resulted in rats' weight loss. Haimeur et al [ 21 ] also found that rats fed with high-fat diet had higher adiposity and adipose tissue/BW ratio compared to those in the control group, but these values were reduced by a dietary supplementation of n-3 PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…Guelzim et al [ 20 ] showed that n-3 PUFAs could improve the body composition and insulin sensitivity and resulted in rats' weight loss. Haimeur et al [ 21 ] also found that rats fed with high-fat diet had higher adiposity and adipose tissue/BW ratio compared to those in the control group, but these values were reduced by a dietary supplementation of n-3 PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…HF diet provided 22 kcal/g, 61 kcal%, 24 kcal% from fat and carbohydrates, respectively; (3) the HF-Phaeo group received a HF diet supplemented with 12% ( w / w ) of freeze-dried microalga P. tricornutum (CNR, Florence, Italy). The microalga supplementation with the dose of 12% was chosen on the basis of previous studies that showed the beneficial effects of the marine microalga O. aurita at 12% after eight weeks of the diet [19,20]. This microalga, which is rich in EPA, prevents metabolic disorders associated with CVD induced by a high-fat diet in Wistar rats [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…in diabetes, dyslipidemia and ischemic heart disease patients led to significant decreases in blood cholesterol, low density lipoproteins (LDL) and very low density lipoproteins (VLDL), triacyglycerols and lipid peroxidation (malondialdehyde, MDA) levels with an improvement in total antioxidant status [16]. In high fat-fed rats, it has been reported that the use of freezedried Odontella aurita, a marine diatom, had a preventive role in dyslipidemia, oxidative stress and platelet aggregation [17] with better results than those observed with fish oil [18], as earlier reported with the microalga Chlorella pyrenoidosa [19]. In diabetic rats, the microalga Isochrysis galbana has been reported to decrease blood levels of glucose, triacylglycerols and cholesterol [20].…”
Section: Introductionmentioning
confidence: 99%